Penyuluhan Kesehatan Tentang Pencehagan Stunting Di Desa Sumare Wilayah Kerja Puskesmas Rangas Kecamatan Simboro Kabupaten Mamuju Tahun 2022 - Safriadi Darmasnyah; Yuliana Yuliana; Musdalifah Musdalifah; Suaib Suaib; Manjaeni Muthia; Sayhril Jadil (Lembaga Pengembangan Kinerja Dosen, 2023)
In accordance with what was stated by Schmidt that stunting is a problem of malnutrition with a sufficiently long period so that growth disturbances appear in children who are lower or shorter (dwarf) than the standard age (Schmidt, 2014). The problem of stunting (failure to thrive) is a serious problem in the development of human resources (HR) in Indonesia. This challenge must be handled properly so that Indonesia's future generations can become superior, competitive and quality generations. The existence of the Covid-19 pandemic has made all the focus on handling it. So that health matters that are more essential and have long-term impacts, such as the problem of stunting, tend to be neglected. The high incidence of stunting in Indonesia, as well as in the West Sulawesi region, is important to conduct health education about stunting prevention for parents of toddlers in Sumare Village, Simboro District, Mamuju Regency. After conducting community service regarding stunting prevention health education, it is hoped that the community will know what stunting is and how to prevent it.